Fecal Changes Following Introduction of Milk in Infants With Outgrowing Non-IgE Cow's Milk Protein Allergy Are Influenced by Previous Consumption of the Probiotic LGG - Guadamuro, Lucía; Diaz, Maria; Jiménez, Santiago; Molinos-Norniella, Cristina; Pérez-Solis, David; Rodríguez, Juan Miguel; Bousoño, Carlos; Gueimonde, Miguel; Margolles, Abelardo; Delgado, Susana; Díaz, Juan José (Frontiers in Immunology, 2019)
Cow`s milk protein allergy (CMPA) is the most common allergy in the first year of life. Non-IgE mediated CMPA is characterized by digestive symptoms and tolerance development before the age of three. Gut microbiota composition in early life has been associated with food allergy. The ingestion of different foods/nutrients may mark different shifts in the microbial colonization of the infant intestine as well as the consumption of probiotics. Aim: to analyze changes in microbiota composition and metabolic and cytokine profiles in fecal samples from infants with non-IgE mediated CMPA after successful milk challenges, tolerance acquisition and increasing dairy introduction in their diet. Methods: Twelve children with CMPA, aged between one and two years old, were recruited for the study. Participants were initially consuming hypoallergenic hydrolyzed formulas (four of them supplemented with the probiotic Lactobacillus rhamnosus GG), before being exposed to a standardized oral challenge (SOC) with cow´s milk. Fecal samples were collected before, one week and one month after performing the SOC. Changes in gut microbiota were determined by high-throughput amplicon sequencing of the 16S rRNA gene. Levels of lactobacilli were also determined by quantitative PCR (qPCR). Microbial metabolites were analyzed by chromatographic methods and fecal cytokines related to the Th1/Th2 balance were determined by immunoassay. Results: Lactic acid bacteria significantly increased in infants who outgrew non-IgE CMPA, after the introduction of milk. Microbial metabolites derived from the fermentation of proteins, such as branched chain fatty acids and p-cresol, diminished. After the SOC, some cytokines related to inflammation (TNF-alpha, IFN-gamma) increased. Accompanying the introduction of an unrestricted diet, we found significant differences in fecal microbial composition, metabolites and cytokines between infants who did not consume the probiotic L. rhamnosus GG and those that did. Conclusions: These findings indicate that the introduction of intact milk proteins is followed by modifications in the infant gut environment through changes in immune mediators, microbiota and its metabolic end-products. Consumption of probiotics during CMPA may contribute to gut homeostasis by fine-tuning these profiles.